JUMLAH, UJI VIABILITAS DAN DAYA KECAMBAH POLEN 31 AKSESI PISANG (Musa sp.) KOLEKSI KEBUN PLASMA NUTFAH PISANG LIPI - Erwin Fajar Hasrianda; Ahmad Zaelani; Yuyu Suryasari Poerba (BERITA BIOLOGI, 2020)
Cross pollination is one of the plant breeding techniques to create a better cultivar with desired traits. A successful cross pollination is affected by quality and quantity of the pollen used. The aim from this study is to know amounts, viability and germination from various banana accessions. This study was conducted by using 31 banana accessions. Pollen quantity per anther, pollen viability, pollen germination growth were measured. The results showed that pollen amounts were ranged between 5.032 and 118.181 pollens per anther. In addition, pollen viability ranged from 30% in Tingalun accession (Musa sp. cv. Tingalun)  to 99% in Malaccensis 2x accession. Furthermore, pollen germination level varied from 1% in Mambee Thu OS accession to 48% in Rutilifes 2x accession. We also found that negative correlation between pollen viability and pollen germination were moderate with correlation coeeficient value of -0,59 ( p-value = 0,00051). From 31 banana accessions tested in this research, pollen source from Malaccensis 2x and Rutilifes 2x banana accessions have the highest potential to be used as the male parent.